Health Hazard From Dust In The Mines And Allied Industries Of The United States-Initial Survey Of The Extent And Severity - M. Van Siclen (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1933)
THE outstanding fact in connection with dust disease in. the United States at present is the growing recognition of its seriousness by state officials and by the more progressive operators of mining, metallurgical and allied industrial plants. The same may perhaps be said of labor in some. of its better organized centers, but the average independent non-. union workman continues, as of yore, to suffer the toll of disability and. even of death from dust inhalation without realization of the source of his ill-being. Progress in the betterment of the handling of sufferers from dust disease and of the conditions creating dust hazards in mining and allied industries is pursuing a course similar to that of the now widespread campaign against accidents, in which the risk is more obvious, more severe, and was naturally recognized sooner. The coming on of dust disease is generally relatively slow and its immediate effects not infre-quently masked by or attributed to other diseases. Marked exceptions to this general rule have occurred in districts where the dust is particularly pernicious, such as the Rand and Joplin; yet such exceptions, unhappy in themselves, opened the eyes of medical men, and of those in other localities charged with the responsibility for the welfare of industry, to the much more widespread if less spectacular hazard existing from the inhalation of. dust in all rock-excavating operations and all industrial operations creating inorganic dust, whether it be crushing and grinding, sand-blast-ing, granite-cutting, or what not. Advancement to date in the United States in prevention and treat-ment has been slow, yet the record shows that quantitative methods for determining the degree of hazard and means for decreasing it were being developed as far back as 25 years ago; and that more rapid progress may be looked for from now on. In 1908, in this country; F. L Hoffman?(1) discussed the mortality from consumption in dusty trades, especially brass foundries; and in 1913.E. R. Hayhurst(2) described the effects of inhalation